Gender, Economy, and the Law: Women Entrepreneurs in Indonesian and Islamic Legal Perspectives - Hidayah, Nur (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2023)
The relationship between women, the economy, and state law in Muslim countries has generated intense debate about whether such laws have promoted or inversely impeded women's rights and gender equality. This study aims to assess women's economic rights, especially in entrepreneurship, in Indonesia from the state and Islamic legal perspectives. It is qualitative research with the juridical and sociological legal approach by analyzing the dimensions of report on entrepreneurship in Women, Business, and the Law 2023 achieved by Indonesia, Law state-related, and Islamic Law. It finds that Indonesia has promoted women's economic rights, including entrepreneurship, in the state law, despite some room for improvement. Women have the same rights to business licenses, enter into contracts or agreements, and open bank accounts, despite a lack of affirmative actions for access to credits for women entrepreneurs. As the biggest Muslim country in the world, Islamic law has influenced such state law. Islam has granted women the right to be self-employed, despite some cultural barriers to achieving gender equality. The government is expected to promote women's economic rights, including the ones on entrepreneurship, and needs to overturn the prevailing gender norms that assign women multiple burdens.